Strengths and Weaknesses of the Russian Concept for the Development of Production and Use of Electric Vehicles Until 2030 - Iosifov, Valeriy I.; Ratner, Pavel D. (International Journal of Energy Economics and Policy, 2022)
Russia has not yet paid due attention to the issues of the transition to electric transport. Only in August 2021, the Russian Government approved a Concept for the development of production and use of electric road transport in the Russian Federation for the period up to 2030. The aim of this study is analysis the Concept from the point of view of world experience in stimulating the development of the electric vehicle market. The study showed that the most elaborated directions of the Concept for the development of production and use of electric road transport in the Russian Federation for the period up to 2030 are the direction of creating a national production of batteries and hydrogen fuel cells, as well as the direction of creating national production facilities and localizing foreign production of electric vehicles, including cars with hydrogen fuel cells. The least developed direction of the Concept is the direction of creating a national base for certification and testing of electric vehicles, which indicates the problem of a lack of competencies in the scientific and technical sphere.